$(p,q)^{th}$ $ψ-$order and $(p,q)^{th}$ $ψ-$type of Entire and Meromorphic Functions and Some of its Estimation - Dibyendu Banerjee; Simul Sarkar (International Journal of Mathematics And its Applications, 2021)
We introduce the concept of $(p,q)^{th}$ $ψ-order$ and $(p,q)^{th}$ $ψ-type$ of entire and meromorphic functions to generalise some results related to the $φ-order$ concept introduced by Chyzhykov-Semochko in [7]. In this paper we establish some estimates of the sum, product and the derivative of entire and meromorphic functions in the complex plane.